2006
DOI: 10.11606/issn.2176-7262.v39i4p554-561
|View full text |Cite
|
Sign up to set email alerts
|

Farmacogenética Do Tratamento De Diabete Melito

Abstract: RESUMO: Diabete melito é uma doença metabólica caracterizada pela deficiência ou resistência de insulina que leva a complicações micro e macrovasculares graves. Fatores genéticos e ambientais contribuem para a etiologia complexa das principais formas de diabete. Os avanços recentes na genética molecular contribuíram para a identificação de vários locos e genes que são relacionados aos subtipos de diabete clinicamente reconhecidos. Este conhecimento tornou-se muito importante para o reconhecimento de pacientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…TCF7L2 gene polymorphisms were also strongly associated with GDM in a recent systematic review published by Zhang et al (2013). The glucokinase (GCK) gene, reported in 16 articles (28%), is responsible for glucose metabolism, with mutations resulting in an impairment of glucose metabolism in beta cells, in turn down-regulating the expression of insulin and hepatic metabolism of glucose (Hirata and Hirata, 2006). A recent study in Scandinavian women showed that a polymorphism in the rs1799884 locus of GCK was associated with GDM (Shaat et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCF7L2 gene polymorphisms were also strongly associated with GDM in a recent systematic review published by Zhang et al (2013). The glucokinase (GCK) gene, reported in 16 articles (28%), is responsible for glucose metabolism, with mutations resulting in an impairment of glucose metabolism in beta cells, in turn down-regulating the expression of insulin and hepatic metabolism of glucose (Hirata and Hirata, 2006). A recent study in Scandinavian women showed that a polymorphism in the rs1799884 locus of GCK was associated with GDM (Shaat et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Various microand macrovascular alterations are among the long-term complications of DM (ADA, 2012). Recent studies have attempted to elucidate the genetic basis of this disorder; in most cases, DM is believed to be multifactorial, caused by both genetic and environmental factors (Hirata and Hirata, 2006). Changing eating habits and a sedentary lifestyle, combined with genetic determinants, play important roles in the pathogenesis of this disease (Bougnères, 2002;Veloso, 2005).…”
Section: Introductionmentioning
confidence: 99%